1999
DOI: 10.1161/01.hyp.34.4.744
|View full text |Cite
|
Sign up to set email alerts
|

Rostral Ventrolateral Medulla

Abstract: Abstract-The major aim of the present study was to evaluate the role of the rostral ventrolateral medulla (RVLM) in the maintenance of hypertension in rats subjected to long-term treatment with N G -nitro-L-arginine methyl ester (L-NAME) (70 mg/kg orally for 1 week). We inhibited or stimulated RVLM neurons with the use of drugs such as glycine, L-glutamate, or kynurenic acid in urethane-anesthetized rats (1.2 to 1.4 g/kg IV). Bilateral microinjection of glycine (50 nmol, 100 nL) into the RVLM of hypertensive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…These results suggest that increased RSNA contributes to hypertension induced by chronic NOS inhibition and that activation of the renin-angiotensin system in the NTS is involved, at least in part, in the increased RSNA via AT 1 receptors (29). The rostral ventrolateral medulla (RVLM), the vasomotor center, is also activated in this model of hypertension, suggesting enhanced central sympathetic outflow (9). Pharmacological inhibition of NOS evoked by N G -monomethyl-L-arginine (L-NMMA) or L-NAME also induces large increases in blood pressure that are partially sympathetically mediated in humans (109).…”
Section: No In the Brainmentioning
confidence: 68%
See 1 more Smart Citation
“…These results suggest that increased RSNA contributes to hypertension induced by chronic NOS inhibition and that activation of the renin-angiotensin system in the NTS is involved, at least in part, in the increased RSNA via AT 1 receptors (29). The rostral ventrolateral medulla (RVLM), the vasomotor center, is also activated in this model of hypertension, suggesting enhanced central sympathetic outflow (9). Pharmacological inhibition of NOS evoked by N G -monomethyl-L-arginine (L-NMMA) or L-NAME also induces large increases in blood pressure that are partially sympathetically mediated in humans (109).…”
Section: No In the Brainmentioning
confidence: 68%
“…Esler (30) reported that the sympathetic nervous system is activated in ϳ50% of patients with hypertension, particularly in patients with essential hypertension. Central sympathetic outflow is determined by several important nuclei and their circuits in the central nervous system (CNS) (9,81). These pathways involve many neurotransmitters and neuromodulators (16,25,38,99).…”
mentioning
confidence: 99%
“…The rostral ventrolateral medulla (RVLM) neurons are activated in rats with chronic NO synthase inhibition. 26 Intracisternal infusion of a drug might affect neurons not only in the NTS but also in the rostral ventrolateral medulla. 27 Therefore, intracisternal infusion of Y-27632 might also alter neuronal activity in areas other than the NTS, such as the rostral ventrolateral medulla in L-NAME-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the potentiation of vasoconstrictor responses to ANG II, which constitutes the important element underlying the slow responses, was also seen in isolated (pump perfused) mesenteric vascular bed (1). It will be impossible here to review the vast amount of data on the controversial aspects of the participation of the central nervous system in angiotensin-induced hypertension (18,37,46,80,120). However, results of several studies reviewed by Krukoff (80) and Patel et al (120) show that the synthesis of NO decreases sympathetic output to periphery in several autonomic nucleus.…”
Section: Effects Of Ang II Oxst and No On The Regulation Of Sympathmentioning
confidence: 99%